Clinical Impact of the Maximum Mean Value of Home Blood Pressure on Cardiovascular Outcomes: A Novel Indicator of Home Blood Pressure Variability. Issue 3 (September 2021) - Fujiwara, Takeshi; Hoshide, Satoshi; Kanegae, Hiroshi; Kario, Kazuomi
Abstract : We assessed the relationship between maximum mean home blood pressure (HBP) and incident cardiovascular disease risks in the general practice population of the J-HOP study (Japan Morning Surge-Home Blood Pressure), which recruited 4231 patients with cardiovascular risk factors (mean [SD] age: 65 [11] years; 53% women; 79% on antihypertensive medications) who measured their HBP in the morning and evening for 14 days. The first day's HBPs were excluded. The average of morning and evening (the average of morning and evening value [MEave]) BP was defined as the average of all HBP values. The maximum mean HBP was defined as the highest value of mean HBP on one occasion. The variability independent of the mean of MEave BP was assessed. The MEave BP was 134/76 mm Hg; the maximum mean HBP was 156/88 mm Hg. Over a median 3.9-year follow-up (16 762 person-years), 72 stroke, and 76 coronary heart disease events occurred. A Cox regression analysis showed that the hazard ratios of a 1-SD increase in maximum mean home systolic BP (SBP; 95% CI) for incident stroke events were (1) 1.89 (1.23–2.89) including MEave SBP and (2) 1.68 (1.33–2.14) including the variability independent of the mean of MEave SBP. These significant associations were not observed for coronary heart disease events. Adding the maximum mean home SBP to the stroke prediction model significantly improved the discrimination: (1) MEave SBP: C statistics difference (95% CI), 0.019 (0.002–0.038); and (2) variability independent of the mean of MEave SBP: 0.031 (0.008–0.056). The maximum mean HBP could be a useful marker for evaluating the stroke risk of patients. Registration: URL: https://upload.umin.ac.jp ; Unique identifier: UMIN000000894 Abstract : Supplemental Digital Content is available in the text.